Dilemmas and actions : self-reports of teachers - Heng, Alice Wang Cheng. (2009)
The purpose of the study is to examine teachers' dilemmas and the ways teachers deal with their perceived dilemmas. An open-ended survey questionnaire was used. Altogether 86 written dilemmas (from 27 primary and 59 secondary teachers) were analyzed.